Pengukuran Kualitas Pelayanan yang Berdampak Terhadap Kepuasan Pelanggan pada Produk Skintific di E-Commerce Shopee yang di Mediasi Kualitas Produk - Zaenabiansyah, Putri Awaliah; Suarsa, Senny Handayani; Diawati, Prety (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
This research aims to determine the effect of product quality on customer satisfaction. The method used is quantitative, the variables to be studied are service quality (X1), product quality (X2) and customer satisfaction (Y). This method uses verification research methods with a quantitative approach. This research method uses primary and secondary data. The population is unknown with a sample of 385 data. The sampling technique used is convenience sampling. Data analysis techniques using SmartPLS software as a data processor using outer model and inner model tests. The results of this study state that service quality has a positive effect on customer satisfaction as a mediator of product quality, so that the H3 hypothesis is accepted and H0 is rejected